Neurogenic Thoracic Outlet Syndrome Reviewed - Ermira PAJAJ; Ridvan ALIMEHMETI; Florian DASHI; Aiola STOJA; Arsen SEFERI (Albanian Journal of Trauma and Emergency Surgery, 2020)
Neurogenic Thoracic Outlet Syndrome (NTOS) is a rare, but controversial syndrome in relation to its diagnosis, treatment modality, and approaches in case of surgical treatment. In the English literature, there are sparse studies dealing with these aspects.